The microbial flora of clinically infected cutaneous metastases: a retrospective study - Virgen, C.A. (Clin Exp Dermatol, 2020)
Symptomatic cutaneous metastases are associated with the symptoms of discharge, malodor, and pain, all of which may negatively impact quality of life and cutaneous health. We conducted a retrospective chart review of patients referred to the Dermatology Service at Memorial Sloan Kettering Cancer Center between August 2006 and June 2015. We characterized the microbial flora and antimicrobial management of cutaneous metastases in 64 patients. We detected pathogenic and/or opportunistic bacteria in 50% of skin lesions. The most commonly isolated organisms were Staphylococcus aureus and Pseudomonas aeruginosa. Patients treated with oral antibiotics, alone or in combination with topical agents, had a statistically significant better improvement in infectious symptoms than those treated without oral antibiotics. Our findings suggest that the normal skin microbial flora is disrupted in patients with symptomatic skin metastases. Oral antibiotics may provide benefit when used as first-line therapy of infected skin lesions in patients with symptomatic cutaneous metastases.